Plumbagin targets the GLUT1/MMP-2 axis to inhibit oral squamous cell carcinoma progression - Fei He; Weiqi Wang; Sadam Ahmed Elayah; Linyang Xie; Ming Yu; Yuxin Gong; Hao Cui; Xiang Liang; Junbo Tu; Ying Han; Sijia Na (Cancer Cell International)
Abstract Aim This study aimed to investigate the clinicopathological characteristics and prognostic value of GLUT1 in oral squamous cell carcinoma (OSCC) and the effect of plumbagin (PLB) on inhibiting OSCC invasion and metastasis through the GLUT1/Matrix Metalloproteinase 2 (MMP2) axis pathway. Materials and methods One hundred and twenty human OSCC specimens were collected. Immunohistochemistry was performed to analyze the expression, clinicopathological characteristics, and prognostic value of GLUT1 in these specimens. Cal27 and SCC9 cell lines were used to investigate the role of PLB in cell proliferation, migration, invasion, and metastasis in vitro and in vivo. Results Immunohistochemistry showed significant associations between GLUT1 expression and MMP2, tumor recurrence, lymphatic metastasis, and TNM stage. In vitro and in vivo experiments demonstrated that PLB inhibited OSCC cell proliferation, migration, and invasion by downregulating GLUT1 and MMP2. WZB117, a GLUT1 inhibitor, also reduced cell colony formation, migration, and invasion. However, univariate and multivariate analyses indicated that GLUT1 expression was not an independent prognostic marker for OSCC overall and disease-free survival. Conclusions The findings demonstrated a novel anti-cancer mechanism of plumbagin, inhibiting OSCC invasion and migration by suppressing the GLUT1/MMP2 axis pathway, providing a theoretical basis for the future clinical use of plumbagin in the treatment of OSCC.